Understanding the Impact of Bathymetric Changes in the German Bight on Coastal Hydrodynamics: One Step Toward Realistic Morphodynamic Modeling - Benjamin Jacob; Emil V. Stanev (Frontiers in Marine Science, 2021)
The hydrodynamic response to morphodynamic variability in the coastal areas of the German Bight was analyzed via numerical experiments using time-referenced bathymetric data for the period 1982–2012. Time-slice experiments were conducted for each year with the Semi-implicit Cross-scale Hydroscience Integrated System Model (SCHISM). This unstructured-grid model resolves small-scale bathymetric features in the coastal zone, which are well-resolved in the high-resolution time-referenced bathymetric data (50 m resolution). Their analysis reveals the continuous migration of tidal channels, as well as rather complex change of the depths of tidal flats in different periods. The almost linear relationship between the cross-sectional inlet areas and the tidal prisms of the intertidal basins in the East Frisian Wadden Sea demonstrates that these bathymetric data describe a consistent morphodynamic evolutionary trend. The numerical experiment results are streamlined to explain the hydrodynamic evolution from 1982 to 2012. Although the bathymetric changes were mostly located in a relatively small part of the model area, they resulted in substantial changes in the M2 tidal amplitudes, i.e., larger than 5 cm in some areas. The hydrodynamic response to bathymetric changes largely exceeded the response to sea level rise. The tidal asymmetry estimated from the model appeared very sensitive to bathymetric evolution, particularly between the southern tip of Sylt Island and the Eider Estuary along the eastern coast. The peak current asymmetry weakened from 1982 to 1995 and even reversed within some tidal basins to become flood-dominant. This would suggest that the flushing trend in the 1980s was reduced or reversed in the second half of the studied period. Salinity also appeared sensitive to bathymetric changes; the deviations in the individual years reached ~22 psu in the tidal channels and tidal flats. One practical conclusion from the present numerical simulations is that wherever possible, the numerical modeling of near-coastal zones must employ time-referenced bathymetry data. The second, perhaps even more important conclusion, is that the progress of morphodynamic modeling in realistic ocean settings with multiple scales and varying bottom forms is strongly dependent on the availability of bathymetric data with appropriate temporal and spatial resolution.